Heat tolerance index, food intake and weight gain of Santa Ines sheep in the agreste region of Pernambuco State, Brazil - doi: 10.4025/actascianimsci.v35i3.18466 - Silva Filho, Florisval Protásio; Azevedo, Marcílio de; Costa, Lígia Alexandrina Barros da; Lana, Ângela Maria Quintão; Ferreira, Marcelo de Andrade; Batista, Ângela Maria Vieira (Acta Scientiarum. Animal Sciences, 2013)
This study evaluated the influence of coat color on the heat tolerance and performance of 21 Santa Inês lambs, non-pregnant, non-lactating, seven animals of each coat color: black, brown and white, with an average initial weight of 25.71, 24.85 and 25.00 kg, for white, brown and black animals, respectively, and 12 months of age. The study was conducted during summer in the agreste region of Pernambuco State, Brazil. Twenty-one sheeps were assigned to a completely randomized design with three treatments and seven replicates. The heat tolerance index and the animal performance were evaluated once a week for eight weeks. White sheep were slightly superior in heat tolerance to brown and black sheep, 88.3, 85.5 and 86.6 respectively, but this was not reflected in the growth performance of the animals, which showed average daily weight gain of 170.10, 193.69 and 199.50 g for animals white, brown and black, respectively.